Concepts For Deferred Tax Accounting - Ancelmus Firdi E. (Center for Economic Studies Universitas Katolik Parahyangan, 2004)
It must be recognized that we are considering tax accounting to be followed in financial statements prepared in accordance with generally accepted accounting principles (GAAP). Financial statements prepared in accordance with tax law and regulation, or fiscal financial statements, may or may not be in accordance with GAAP. Their primary purpose is to be used as a basis for determination of tax liability or compliance, not a fair presentation of financial position or results of operations. Only when the difference between GAAP and tax rules are not material should tax basis statements be considered to be in accordance with GAAP. Tax Payable (Liability) Method is widely used in Indonesia since it is one of the methods of tax accounting that In line with Indonesian Accounting Standard. (SAK). However this method did not consider the future effects of timing differences between net income accounting based calculation versus net income tax based calculation. Another Liability Method, which is part of deferred tax accounting, was the right method if we want to consider any future tax effect exist because of timing differences.